Overcoming the saving slump : how to increase the effectiveness of financial education and saving programs - Lusardi, Annamaria (University of Chicago Press, 2008)
Mapping the changing landscape of pensions and the rise of defined contribution plans, this book investigates methods for stimulating saving and promoting financial education, drawing on the experience of the United States as well as countries that have privatized their welfare systems, including Sweden and Chile.